2020
DOI: 10.1108/ijtc-08-2019-0148
|View full text |Cite
|
Sign up to set email alerts
|

Overtourism in Indian cities: a case study of Nainital

Abstract: Purpose This study aims to address the issue of overtourism, its causes and impacts and propose a strategy based on a theoretical overtourism matrix to be applied to the Nainital city. Design/methodology/approach Reports on rules and regulations from government authorities, court orders and newspaper reports were studied to understand the severity of overtourism. Focus interviews were undertaken, and monthly tourist arrival data for 13 years is analysed to gauge the levels of overtourism. Findings The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The fast growing interest of tourists in spending their time in cities brings problems that were not observed in tourist resorts or wildlife destinations [27,28]. Often, the problem of overtourism is attributed to cities [29,30]. The tourism product offered in cites is very complex and specific.…”
Section: Introductionmentioning
confidence: 99%
“…The fast growing interest of tourists in spending their time in cities brings problems that were not observed in tourist resorts or wildlife destinations [27,28]. Often, the problem of overtourism is attributed to cities [29,30]. The tourism product offered in cites is very complex and specific.…”
Section: Introductionmentioning
confidence: 99%
“…The development of successive factors is taken from several previous studies. So that, the factors are included in driving of tourism area are telecommunication, power source, transportation, waste management [11], [12], location, clean water source, supporting industry, spatial, hospitality, safety and security [13], [14], and stakeholder [15]. To support defense strategies and tourism management during a pandemic in the new normal era, tourism destinations apply adequate standards for tourists [16], thus providing alternative new travel patterns: (i) high standard security: Increasing security standards such as checking luggage, the installation of CCTV on each side of the tourist attraction throughout the region, and the addition of security personnel such as security guards in all tourist attractions [17].…”
Section: Resultsmentioning
confidence: 99%
“…Pröbstl-Haider et al (2021) observed that extreme summer could have an impact on the tourist consumption of outdoor activities. Over-tourism in mountain destinations is a common phenomenon because of the extreme heat in the plains (Barbhuiya, 2021). Practitioners must adopt GIS to monitor the changes in climatic conditions and observe any future abnormalities.…”
Section: Cluster 4: Climate Change and The Future Of Mountain Tourismmentioning
confidence: 99%